Tone at the top: leadership makeover and ESG focus in Indian private banks - Saibal Ghosh (20552052) (2025)
Using a sample of listed private banks in India, the paper quantitatively investigates the issue of leadership makeover in Indian private banks and identifies its impact on ESG scores, including the individual pillars within the corporate governance framework. Using secondary data for 2011–2023, the findings indicate a positive and statistically significant impact of leadership makeover on ESG scores. The response differs across new and old private banks, as also concerning the pillars of ESG. In particular, freshly appointed CEOs in new private banks emphasise the environmental and social pillars of ESG, whereas CEOs of old private banks focus on the governance pillar. There is also a honeymoon versus consolidation phase, wherein CEOs in new private banks are typically proactive in the former phase, while those in old private banks have a more long-term approach. These findings suggest that the differential performance of private banks on the ESG score can be traced to CEO individualism, which is consistent with the Upper Echelons theory. Other Information Published in: International Journal of Disclosure and Governance License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1057/s41310-024-00278-9